Self-Habilitation in Consistency of Reading The Qur'an in In The Masjid Al-Qodri: Action Research in Society - Muhammad Iqbal; Muhammad Aswin Pohan; Daffa Faishal Suwita; Muhammad Ikhwan Mustaqim; Muhammad Ibnu Alwi (As-sunnah: Jurnal Pengabdian Masyarakat, 2023)
It is undeniable that almost all Muslims have the Al-Quran, but, regrettably, the Quran is not read but only used as a display, either because it has been stored for a long time and has never been read, or because they cannot read it. This community service activity by students and lecturers of STAI As-Sunnah aims to revive people's interest in reading the Quran. This community service activity was created using an action research framework. Furthermore, the method used is Participatory Action Research, which is commonly used to help solve social problems. Which is research commonly used to help solve social problems in society. In this study, it was found that it turns out that community interest can be reshaped through positive Al-Quran-based activities carried out over several cycles. It can be concluded that many social factors cause the lack of interest in reading the Quran. However, this interest can still be raised and revived through Al-Quran-based activities by the STAI As-sunnah team.